The Sublethal Effects of Blatella germanica Infected with Metarizhium anisopliae and Beauveria bassiana on Its Offspring - Sanjaya, Yayan; Saefudin, Saefudin; Kusnadi, Kusnadi; Suhara, Suhara; Shani, Nadiya Syafia (-, 2024)
The sublethal effect of Blatella germanica infected with Metarhizium anisopliae, Beauvaria bassianna, and Spicaria on its offspring has been carried out. It is known that the LC50 value of each fungus is 106. This study aims to determine the extent of the sublethal effect on the duration of ootheca formation, the number of ootheca, and the number of ootheca produced. The ‘Dipping method’ was used with three treatments and five replications. The results showed that the sub-lethal effect influenced the duration of ootheca formation. Metarhizium anisopliae and Beauveria bassiana affected the start of ootheca formation when compared to the control (25.95 days), the length of time needed for ootheca that produced nymphs in Metarhizium anisopliae and Beauveria bassiana exposure compared to the control (6 days) and the number of nymphs caused by Metarhizium anisopliae and Beauveria bassiana produced fewer nymphs than the control (29.25 days).